A Simulated Kalman Filter Optimizer with White Hole Operator - Khairi Mohammed, Suad; Muhammad, Badaruddin; Azlina Ab. Aziz, Nor; Hidayati Abdul Aziz, Nor; Ab Rahman, Tasiransurini; Subari, Norazian; Saberi Mohamad, Mohd; Ibrahim, Zuwairie (International Journal of Engineering and Technology, 2018)
The simulated Kalman filter (SKF) is a population-based optimization algorithm that was developed based on a well-known estimator called Kalman filter. Meanwhile, a white hole operator has been recently introduced to prevent premature convergence in black hole algorithm (BHA). The computation of white hole operator begins by selecting the worst agent as the white hole with event horizon. If an agent is located within the event horizon of white hole, the agent is pushed by the white hole. In this study, the white hole operator is used to improve the effectiveness of the SKF optimizer. A comprehensive experiment is done to evaluate the proposed SKF with white hole operator (SKFWH).Â Â